ZAKAT EMPOWERMENT THROUGH THE EMPOWERED VILLAGE PROGRAM: IMPLICATIONS FOR MUSTAHIK WELFARE - Nur Efendi; Ahmad Hasan Ridwan; Mohamad Anton Athoillah; Ending Solehudin; Neneng Nurhasanah; Cecep Soleh Kurniawan (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2026)
One of the main challenges in zakat utilization is creating sustainable impacts that enable mustahik to improve their socioeconomic conditions. This study analyzes the zakat empowerment strategy implemented through the Desa Berdaya (Empowered Village) program of Rumah Zakat and examines its impact on mustahik welfare from both material and spiritual perspectives. This study employs a mixed-methods approach. Qualitative data were analyzed using descriptive and SWOT analyses to examine the empowerment model, while quantitative analysis utilized the CIBEST Index to measure changes in mustahik welfare. The findings indicate that the Desa Berdaya strategy is based on three key approaches: continuous mentoring through village facilitators (Relawan Inspirasi), integrated empowerment programs tailored to local potential, and the optimization of community-owned village enterprises (BUMMAS). SWOT results place the program in Quadrant I, reflecting strong growth potential and opportunities for further development. The CIBEST analysis shows substantial improvements in welfare after participation in the program. Material welfare increased by 12%, spiritual welfare by 89%, the absolute poverty index decreased by 91%, and the overall welfare index improved by 145%. These results demonstrate that Desa Berdaya is an effective model of productive zakat utilization that contributes to sustainable poverty reduction and community empowerment. The study also underscores the importance of expanding productive zakat allocation to maximize long-term welfare outcomes.